2018
DOI: 10.1038/s41598-018-30328-6
|View full text |Cite
|
Sign up to set email alerts
|

Silkworms suppress the release of green leaf volatiles by mulberry leaves with an enzyme from their spinnerets

Abstract: In response to herbivory, plants emit a blend of volatile organic compounds that includes green leaf volatiles (GLVs) and terpenoids. These volatiles are known to attract natural enemies of herbivores and are therefore considered to function as an indirect defense. Selection should favor herbivores that are able to suppress these volatile emissions, and thereby make themselves less conspicuous to natural enemies. We tested this possibility for silkworms, which were observed to leave secretions from their spinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…This is mainly because those stresses may individually alter the production of GLV. For example, many insect herbivores modulate GLV emissions through factors abundant in their saliva [41][42][43][44]. Furthermore, cold stress will, as long as its ongoing, likely reduce enzyme activities, including those involved in GLV production [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly because those stresses may individually alter the production of GLV. For example, many insect herbivores modulate GLV emissions through factors abundant in their saliva [41][42][43][44]. Furthermore, cold stress will, as long as its ongoing, likely reduce enzyme activities, including those involved in GLV production [46].…”
Section: Discussionmentioning
confidence: 99%
“…This is of critical importance when performing meaningful experiments with the respective plant, which is always a matter of controversy. Furthermore, in light of recent discoveries on how insect herbivores suppress the production of GLV [41][42][43][44], knowledge about the amounts of GLV that can be produced by the respective plant species is essential in assessing the effectiveness of this suppression. We analyzed the composition of those GLVs with focus on the aldehydes (Z-3-HAL, E-2-HAL, and hexanal), mainly because other GLVs downstream are not produced by damaged tissue since they require intact cells for their biosynthesis [24].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, glucose oxidase in H. zea saliva can inhibit the synthesis and functionality of nicotine in tobacco (Nicotiana attenuata) and thus decrease resistance [21,47]. Insect-derived molecules can also suppress indirect defences, as it has been shown that a silkworm (Bombyx mori) specific enzyme (BmFHD) suppressed the production of leaf VOCs in mulberry (Morus alba) [48]. In order to realise the nature of the complexities associated with insect feeding, development of techniques that enable the uncoupling of the mechanisms that drive the responses observed in plants is critical.…”
Section: The Chemical Machinery Of Plant Defencesmentioning
confidence: 99%
“…To compare insect herbivory both in the presence and absence of insect saliva, ablation of the salivary glands, and thus prevention of salivation, is employed [19,21,48,96]. This method is unique in that it uses true herbivory for both treatments and controls.…”
Section: Ablationmentioning
confidence: 99%
“…For example, some compounds are emitted rapidly following initiation of damage while production of other compounds may be delayed by several hours (Erb et al, 2015;Joo et al, 2018;Ponzio, Gols, Pieterse, & Dicke, 2013). Some studies have observed stronger production of HIPVs with increased herbivore damage (De Boer, Hordijk, Posthumus, & Dicke, 2008;Dicke, Van Loon, & Soler, 2009;Maeda & Takabayashi, 2001) while others have reported suppression of HIPVs with continuous feeding (Alba, Glas, Schimmel, & Kant, 2011;Desurmont et al, 2014;Takai et al, 2018). The temporal dynamics of plant volatile production 5.…”
Section: Introductionmentioning
confidence: 99%